Tourism and Collecting in Kyoto: The Miyako Hotel as an Agent in the Creation of the Hon. Henry Marsham Collection of Japanese Art, Maidstone Museum, Kent - Ai Fukunaga (Journal for Art Market Studies, 2018)
The Hon. Henry Marsham (1845-1908) was a British businessman who collected Japanese works of art in Kyoto during the 1900s. His Kyoto ware collection at Maidstone Museum, Kent, is superior in both quantity and quality to other collections in Japan and overseas. The over 700 ceramic works in this collection range from daily dishes and tea vessels to utensils exclusively made for noble families. Marsham assembled the objects in a transnational process which was instigated in Japan before it continued in Britain. He collected Japanese works with local support before sending his collection to the Kentish provincial museum, with which he communicated closely on matters of arrangement and display. This paper examines the role of the Miyako Hotel, as an actor in creating Marsham’s collection as well as his Kyoto network for collecting. The interactions between the British collector and the local agents are illustrated based on letters and manuscript notes in his archive at the Maidstone Museum. The actors from the empirical study are then discussed in the context of Kyoto and the emerging tourist industry in the late Meiji era, complemented by the research of local newspaper articles of the time. Understanding collecting as a collaborative process by actors in different sectors, the network of collecting is contextualised here for both the collector and the people in Meiji Kyoto.